The Benefit of Digital Literacy for English Literature Students - Merry Rullyanti; Lina Tri Astuty Beru Sembiring; Viki Mahdiansyah; Rike Monike (UNIVED Press, 2021)
This research purposed to examine the benefits of digital competency and e-learning during the Pandemic that interrupted schooling. Expert opinions published in different international publications were used to address the question. The core of our results from a wide range of subjects, including the benefits of digital literacy, is that it is undoubtedly capable of innovating learning that has been disrupted since the Pandemic struck the globe. Although expert opinions differ significantly, the abilities of pupils and other educators in digital technology are so essential that educational disruption will be very fearful. To address the research's topic, the researchers looked for data in the literature and then performed a study that included coding systems, theme verification, assessment, and in-depth interpretation. This is qualitative research that takes a phenomenological approach touts design. The findings showed that digital literacy is defined as students’ capacity to arrange knowledge in the world of learning, from seeking to communicating, with little instructor assistance. This document includes, among other things, a summary of the study's results with the hopes of providing more information for educators and educational researchers interested in using digital literacy to innovate teaching during the Pandemic. Keyword: Digital Literacy, e-learning, students’ learning